Reorganisation of primary care for older adults during COVID-19: a cross-sectional database study in the UK - Joy, Mark; McGagh, Dylan; Jones, Nicholas; Liyanage, Harshana; Sherlock, Julian; Parimalanathan, Vaishnavi; Akinyemi, Oluwafunmi; van Vlymen, Jeremy; Howsam, Gary; Marshall, Martin; Hobbs, Fd Richard; de Lusignan, Simon (British journal of general practice, 2020)
The coronavirus disease 2019 (COVID-19) pandemic has resulted in a rapid change in workload across healthcare systems. Factors related to this adaptation in UK primary care have not yet been examined. To assess the responsiveness and prioritisation of primary care consultation type for older adults during the COVID-19 pandemic. A cross-sectional database study examining consultations between 17 February and 10 May 2020 for patients aged ≥65 years, drawn from primary care practices within the Oxford Royal College of General Practitioners (RCGP) Research and Surveillance Centre (RSC) sentinel network, UK. The authors reported the proportion of consultation type across five categories: clinical administration, electronic/video, face-to-face, telephone, and home visits. Temporal trends in telephone and face-to-face consultations were analysed by polypharmacy, frailty status, and socioeconomic group using incidence rate ratios (IRR). Across 3 851 304 consultations, the population median age was 75 years (interquartile range [IQR] 70-82); and 46% ( = 82 926) of the cohort ( = 180 420) were male. The rate of telephone and electronic/video consultations more than doubled across the study period (106.0% and 102.8%, respectively). Face-to-face consultations fell by 64.6% and home visits by 62.6%. This predominantly occurred across week 11 (week commencing 9 March 2020), coinciding with national policy change. Polypharmacy and frailty were associated with a relative increase in consultations. The greatest relative increase was among people taking ≥10 medications compared with those taking none (face-to-face IRR 9.90, 95% CI = 9.55 to 10.26; telephone IRR 17.64, 95% CI = 16.89 to 18.41). Primary care has undergone an unprecedented in-pandemic reorganisation while retaining focus on patients with increased complexity.